Palestinian Narratives of Silence andConsciousness Raising: A Critical Study of Mourid Barghouti’s Autobiographies - Mavra Ahmed; Saiyma Aslam (NUML Journal of Critical Inquiry)
Giving voice to suppressed stories and experiences becomes significantly instrumental in defining and shaping the identity and history of the oppressed. In this article, therefore, we study Mourid Barghouti autobiographical narratives, I Saw Ramallah (2005) and I was Born There, I was Born Here (2011), to present and examine the suppression of Palestinians living within Palestine as well as in exile. Our study attempts to give voice to the Palestinians’ daily struggle by documenting their lived stories and experiences. Instead of focusing only on the autobiographer’s excursion, we also explore the characters’ trajectories into consciousness. In order to study how autobiographical narratives have the power to change the self and others, we premise our discussion on the theoretical nexus provided by Sidonie Smith and Julia Watson (2001) and Ken Plummer (1995). With our focus on the producer of the autobiographies, these theorists help us examine how Barghouti actively engages in registering his protest against the silencing of Palestinians in Israel and raising his and his people’s consciousness (together) with that of the rest of the world through the act of reading his life narratives.